Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

For (1), pick some numbers. A = 7, B = 3, C = 4, D = 6 → C + B = 7 A = 1, B = 9, C = 3, D = 7 → C + B = 12 No single value Insufficient.

For (2), It does not even contain the variable C. Insufficient. Combined: Notice in this problem that there are several sets of 2 variable terms and they're all equal. From (2), (D – B) = (E + F) → C + D = D–B. Add B to both sides and subtract D from both sides → C + B = 0. Sufficient.

Hi, I want to know if we can solve Statement (1) without pick number, please. I think it does not have C + B in equation, it is insufficient.

Re: What is the value of C + B? (1) A + B = C + D = E + F [#permalink]

Show Tags

05 Feb 2014, 16:20

1

This post received KUDOS

Let me try,

We can rearrange the equations:

C = E+F - D B = E+F - A

All 3 equalities given would boil down to this,

C+B = 2 (E+F) - (A+D)

So C+B depends on 4 different variables which are still unknown. In other words there are infinitely many number of possibilities for C+B when the Statement 1 alone is considered.

For (1), pick some numbers. A = 7, B = 3, C = 4, D = 6 → C + B = 7 A = 1, B = 9, C = 3, D = 7 → C + B = 12 No single value Insufficient.

For (2), It does not even contain the variable C. Insufficient. Combined: Notice in this problem that there are several sets of 2 variable terms and they're all equal. From (2), (D – B) = (E + F) → C + D = D–B. Add B to both sides and subtract D from both sides → C + B = 0. Sufficient.

Hi, I want to know if we can solve Statement (1) without pick number, please. I think it does not have C + B in equation, it is insufficient.

You don't really need to do anything in statement (1)

(1) A + B = C + D = E + F Each equation you can make has 4 different variables in it. We don't have the value of any variable. Hence, there is no way you can find the value of B+C. B and C could innumerable values and their sum could be anything.

Using both statements together, A + B = C + D = E + F (E + F) = (D – B), focus on B and C and eliminate as many variables as you can

For (1), pick some numbers. A = 7, B = 3, C = 4, D = 6 → C + B = 7 A = 1, B = 9, C = 3, D = 7 → C + B = 12 No single value Insufficient.

For (2), It does not even contain the variable C. Insufficient. Combined: Notice in this problem that there are several sets of 2 variable terms and they're all equal. From (2), (D – B) = (E + F) → C + D = D–B. Add B to both sides and subtract D from both sides → C + B = 0. Sufficient.

Hi, I want to know if we can solve Statement (1) without pick number, please. I think it does not have C + B in equation, it is insufficient.

You don't really need to do anything in statement (1)

(1) A + B = C + D = E + F Each equation you can make has 4 different variables in it. We don't have the value of any variable. Hence, there is no way you can find the value of B+C. B and C could innumerable values and their sum could be anything.

Using both statements together, A + B = C + D = E + F (E + F) = (D – B), focus on B and C and eliminate as many variables as you can

you get C + D = D - B B + C = 0

Answer (C)

Statement 1 and 2 both are insufficient to get the value C-B..

Happy New Year everyone! Before I get started on this post, and well, restarted on this blog in general, I wanted to mention something. For the past several months...

It’s quickly approaching two years since I last wrote anything on this blog. A lot has happened since then. When I last posted, I had just gotten back from...

Post-MBA I became very intrigued by how senior leaders navigated their career progression. It was also at this time that I realized I learned nothing about this during my...